UPAYA MENINGKATKAN MINAT BELAJAR ANAK MELALUI PEMBELAJARAN SAINS - Aulia Akmal (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
This study examines the low learning interest in children in teaching and learning in the classroom. The purpose of his research is to investigate efforts to increase children's interest in learning through science learning. This research uses classroom action research methods. The subject of the research was the group of B5 kindergarten YLPI Marpoyan, Pekanbaru totaling 23 children carried out in the 2017/2018 school year. Data collection techniques through observation, interviews, and documentation. The research component uses four stages, namely planning, action, observation, and reflection contained in two cycles which are analyzed by qualitative research methods. The results showed an increase in interest in learning based on pre-research results, cycle I, and cycle II. Seen in the increase in student interest in learning with a very good category from none of the students to 6 students (21.7%) and the good category also increased interest in learning from 6 students (26.1%) in the first cycle and there were 15 students (65,2%) in the second cycle. This study was stated to have met the success criteria above 80% on good and very good criteria.